Development and validation of spectrophotometric methods for simultaneous estimation of citicoline and piracetam in tablet dosage form - Akhila Sivadas; Aiswarya Sathi; Kavya Sathi; Kalpana Pravin Rahate (Wolters Kluwer Medknow Publications, 2013)
Context: Citicoline (CN) and piracetam (PM) combination in tablet formulation is newly introduced in market. It is necessary to develop suitable quality control methods for rapid and accurate determination of these drugs. Aim: The study aimed to develop the methods for simultaneous determination of CN and PM in combined dosage form. Materials and Methods: The first method was developed by formation and solving simultaneous equations using 280.3 and 264.1 nm as two analytical wavelengths. Second method was absorbance ratio in which wavelengths selected were 256.6 nm as its absorptive point and 280.3 nm as λmax of CN. According to International Conference on Harmonization (ICH) norm, the parameters - linearity, precision, and accuracy were studied. The methods were validated statistically and by recovery studies. Results: Both the drugs obeyed Beer-Lambert's law at the selected wavelengths in concentration range of 5-13 μg/ml for CN and 10-22 μg/ml for PM. The percentage of CN and PM in marketed tablet formulation was found to be 99.006 ± 0.173 and 99.257 ± 0.613, respectively; by simultaneous equation method. For Q-Absorption ratio method the percentage of CN and PM was found to be 99.078 ± 0.158 and 99.708 ± 0.838, respectively. Conclusions: The proposed methods were simple, reproducible, precise and robust. The methods can be successfully applied for routine analysis of tablets.